2018
DOI: 10.1016/j.ekir.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Patients With Chronic Renal Disease Without Health Insurance in Mexico: Opportunities for a National Renal Health Policy

Abstract: IntroductionDespite a systematic increase in the coverage of patients with end-stage renal disease (ESRD) who have received dialytic therapies and transplantation over the past 2 decades, the Mexican health system currently still does not have a program to provide full coverage of ESRD. Our aim was to analyze mortality in patients with ESRD without health insurance.MethodsThis was a prospective cohort study of 850 patients with advanced chronic kidney disease (CKD). Risk factors associated with death were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 32 publications
2
20
0
4
Order By: Relevance
“…25 One recent study reported that the 3-year mortality rate of CKD patients requiring RRT in Mexico who did not have social security was 56.7%. 48 Those patients who did have a health service providing RRT showed a 3-year mortality rate of 38.2%. 48 Thus, patients without health insurance were 2.64 times more likely to die from CKD than those who did.…”
Section: Open Accessmentioning
confidence: 97%
See 2 more Smart Citations
“…25 One recent study reported that the 3-year mortality rate of CKD patients requiring RRT in Mexico who did not have social security was 56.7%. 48 Those patients who did have a health service providing RRT showed a 3-year mortality rate of 38.2%. 48 Thus, patients without health insurance were 2.64 times more likely to die from CKD than those who did.…”
Section: Open Accessmentioning
confidence: 97%
“…48 Those patients who did have a health service providing RRT showed a 3-year mortality rate of 38.2%. 48 Thus, patients without health insurance were 2.64 times more likely to die from CKD than those who did. 48 Therefore, socioeconomically disadvantaged…”
Section: Open Accessmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, mortality rate was higher in patients without health insurance than patients with health insurance (56.6% vs 38.2%). This alarming data reflects the fact that uninsured patients with intermittent modalities and poor economic conditions experience the worst outcomes 16 .…”
mentioning
confidence: 99%
“…Thirteen years after our first report that highlighted the disparities of access to renal replacement therapy (RRT) in the Mexican population, 1 the study by Valdez-Ortiz et al. 2 indicates that nothing has changed to improve access and quality of care to end-stage renal disease (ESRD) patients in Mexico.…”
mentioning
confidence: 99%